Preclinical model systems of ryanodine receptor 1-related myopathies and malignant hyperthermia: a comprehensive scoping review of works published 1990–2019 - Lawal, Tokunbor A. (Orphanet J Rare Dis, 2020)
BACKGROUND: Pathogenic variations in the gene encoding the skeletal muscle ryanodine receptor (RyR1) are associated with malignant hyperthermia (MH) susceptibility, a life-threatening hypermetabolic condition and RYR1-related myopathies (RYR1-RM), a spectrum of rare neuromuscular disorders. In RYR1-RM, intracellular calcium dysregulation, post-translational modifications, and decreased protein expression lead to a heterogenous clinical presentation including proximal muscle weakness, contractures, scoliosis, respiratory insufficiency, and ophthalmoplegia. Preclinical model systems of RYR1-RM and MH have been developed to better understand underlying pathomechanisms and test potential therapeutics. METHODS: We conducted a comprehensive scoping review of scientific literature pertaining to RYR1-RM and MH preclinical model systems in accordance with the PRISMA Scoping Reviews Checklist and the framework proposed by Arksey and O’Malley. Two major electronic databases (PubMed and EMBASE) were searched without language restriction for articles and abstracts published between January 1, 1990 and July 3, 2019. RESULTS: Our search yielded 5049 publications from which 262 were included in this review. A majority of variants tested in RYR1 preclinical models were localized to established MH/central core disease (MH/CCD) hot spots. A total of 250 unique RYR1 variations were reported in human/rodent/porcine models with 95% being missense substitutions. The most frequently reported RYR1 variant was R614C/R615C (human/porcine total n = 39), followed by Y523S/Y524S (rabbit/mouse total n = 30), I4898T/I4897T/I4895T (human/rabbit/mouse total n = 20), and R163C/R165C (human/mouse total n = 18). The dyspedic mouse was utilized by 47% of publications in the rodent category and its RyR1-null (1B5) myotubes were transfected in 23% of publications in the cellular model category. In studies of transfected HEK-293 cells, 57% of RYR1 variations affected the RyR1 channel and activation core domain. A total of 15 RYR1 mutant mouse strains were identified of which ten were heterozygous, three were compound heterozygous, and a further two were knockout. Porcine, avian, zebrafish, C. elegans, canine, equine, and drosophila model systems were also reported. CONCLUSIONS: Over the past 30 years, there were 262 publications on MH and RYR1-RM preclinical model systems featuring more than 200 unique RYR1 variations tested in a broad range of species. Findings from these studies have set the foundation for therapeutic development for MH and RYR1-RM.